Analysis on the main controlling factors of water-flowing fracture evolution in deep-buried and thick bedrock. Issue 1 (November 2020) - Zheng, Chao; Yu, Lan; Sun, Ning
Abstract: The study on the evolution and development law of mining disturbed overlying rock fissures is the basic theory for mine water prevention and gas drainage. In order to reveal the evolution law of water conducting cracks in bedrock after deep burial, through the in-situ measurement of mining cracks in overlying strata in Huanglong mining area, the structural characteristics of overlying strata are calculated and analyzed by using key layer theory. It is found that the development height and shape of mining fissures are controlled by 8 direct influencing factors such as mining thickness and 10 indirect influencing factors such as subsidence space, in which mining size and roof overburden structure are the main control indexes. The development pattern of mining fracture is "trapezoid". For the structural characteristics of roof overlying strata, this paper puts forward the ratio of soft rock proportion coefficient and permeability coefficient in the key layer load layer based on the key layer theory, which plays an important role in the actual development height of mining fissures and the incidence of water inrush.